DNA methyltransferase 1 inhibits O6-methylguanine-DNAmethyl-transferase-mediated cell growth and metastasis of hypopharyngeal squamous carcinoma. (August 2021) - Tian, Ruxian; Lv, Yayun; Yang, Xin; Cui, Limei; Wu, Xinxin; Liu, Chuan; Li, Jingjing; Yao, Yao; Yang, Yujuan; Mou, Yakui; Song, Xicheng
Highlights: DNMT1 overexpression and MGMT downexpression in hypopharyngeal squamous carcinoma. Aberrant expression of DNMT1 & MGMT affects clinical characteristics of this tumor. Silencing of DNMT1 inhibits proliferation and metastasis, and induces apoptosis. DNMT1 knockdown upregulates MGMT expression by reversing its promoter methylation. Abstract: Objective: To explore the role of DNA methyltransferase 1 (DNMT1) in development and progression of hypopharyngeal squamous carcinoma. Design: A total of 32 hypopharyngeal squamous carcinoma biopsy samples and 20 normal tissue specimens were collected. Immunohistochemical staining, quantitative real-time polymerase chain reaction, and Western blot were performed for expression analysis. The mRNA and protein expression in the specimens and subcellular localization were analyzed. hypopharyngeal squamous carcinoma cells (FaDu) were used for small interfering RNA of DNMT1, and proliferation, cell cycle, and apoptosis were determined in the transfected cells. Furthermore, metastatic ability and methylation status of O 6 -methylguanine-DNAmethyl-transferase (MGMT) promoter was assessed. Results: Our results showed that DNMT1 was overexpressed, while MGMT was down expressed in hypopharyngeal squamous carcinoma. DNMT1 overexpression and MGMT down expression were significantly associated with poorly differentiated tumors, lymph node metastasis, and clinical stage. DNMT1 and MGMT were majorly distributed in the nucleus. Furthermore, knockdown of DNMT1 inhibited proliferation and metastasis, induced apoptosis and G1 phase arrest in FaDu cells, and upregulated MGMT expression to reverse methylation status of MGMT promoter. Conclusions: This study for the first time demonstrated the clinical value and the role of DNMT1 and MGMT in the biological function of hypopharyngeal squamous carcinoma. This work suggested that DNMT1 might serve as a potential therapeutic target for patients with hypopharyngeal squamous carcinoma.